Electrocatalytic activity of composite Fe/TiO2 electrodeposits for hydrogen evolution reaction in alkaline solutions. (18th May 2016) - Danilov, F.I.; Tsurkan, A.V.; Vasil'eva, E.A.; Protsenko, V.S.
Abstract: Fe/TiO2 composite coatings were obtained by electrodeposition using a methanesulfonate plating bath containing colloidal TiO2 particles. Iron/titania electrodeposited composites exhibited enhanced electrocatalytic activity towards hydrogen and oxygen evolution reactions (HER and OER) in an alkaline solution. The electrocatalytic properties of Fe/TiO2 composites towards the HER were studied by means of voltammetry, electrochemical impedance spectroscopy and chronoamperometry methods. An increase in TiO2 content in iron matrix resulted in an increase in the electrocatalytic activity. The kinetic parameters were calculated on the basis of Tafel plots and EIS measurements and the possible mechanisms of the HER and OER were considered. The hydrogen evolution reaction on Fe/TiO2 electrodes obeyed Volmer–Heyrovsky mechanism. It was concluded that the increase in the rate of the HER and OER on Fe/TiO2 composite electrodes may be associated with the emergence of the redox couples on the electrode surface and the growth of the concentration of the surface active sites. The Fe/TiO2 electrocatalysts showed a good catalytic stability in the HER and OER in 1 M NaOH solution. Highlights: Fe/TiO2 composites (up to 5% of TiO2 ) are electrodeposited from methanesulfonate bath. Electrodeposition of Fe/TiO2 composites complies with Guglielmi's model. Fe/TiO2 coatings show high electrocatalytic activity towards HER and OER in 1 M NaOH. An increase in electrocatalytic activity with increasing TiO2 content in coatings. Hydrogen evolution reaction on Fe/TiO2 electrodes obeys Volmer–Heyrovsky mechanism.